The debate on divorce in the Arequipa press (1918-1930) - Moreno Cavero, Renzo (2022)
The proposal to make divorce possible in Peru resulted in strong debates, because it profoundly affected the family. Opposing views came from two groups which were traditionally in confrontation: liberals and conservatives. The city of Arequipa took active part in the public debate. This study researches the views of two important local Arequipa journals: «El Deber» and «El Derecho». The first rejected divorce, strongly defending the indissolubility of marriage; the second supported the promotion and establishment of divorce in Peru. This study shows the vibrant intellectual production in Arequipa during the first decades of the twentieth century, expressed through the press, as well as it's strong involvement in nationwide issues.